2022
DOI: 10.1101/2022.01.24.477633
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Binding of Human ACE2 and RBD of Omicron Enhanced by Unique Interaction Patterns Among SARS-CoV-2 Variants of Concern

Abstract: The 2019 coronavirus disease (COVID-19) pandemic has had devastating impacts on our global health. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the virus causing COVID-19, has continued to mutate and spread worldwide despite global vaccination efforts. In particular, the Omicron variant, first identified in South Africa in late November 2021, has now overtaken the Delta variant and become the dominant strain worldwide. Compared to the original strain identified in Wuhan, Omicron features 50 ge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 33 publications
3
25
0
Order By: Relevance
“…While it has been suggested in a large meta-analysis that ethnicity also plays a role in susceptibility of infected individuals for loss of smell and taste, and that individuals of Asian origin are less prone to it (7), viral factors appear to have a much larger role than host factors (54). In comparison to alpha and delta, omicron harbors even more mutations in the spike protein including regions of the RBD involved in ACE2 binding and around the furin cleavage site, and has been shown to have high ACE2 binding affinity (55). Interestingly, however, omicron exhibits an inefficient use of the cellular protease TMPRSS2, which is required for proteolytic cleavage of the spike protein at the S2' site to liberate the fusion peptide, and relies more strongly on the endosomal uptake route (56), suggesting that ACE2/ TMPRSS2-expressing cells would no longer be as strongly preferred target cells.…”
Section: Discussionmentioning
confidence: 99%
“…While it has been suggested in a large meta-analysis that ethnicity also plays a role in susceptibility of infected individuals for loss of smell and taste, and that individuals of Asian origin are less prone to it (7), viral factors appear to have a much larger role than host factors (54). In comparison to alpha and delta, omicron harbors even more mutations in the spike protein including regions of the RBD involved in ACE2 binding and around the furin cleavage site, and has been shown to have high ACE2 binding affinity (55). Interestingly, however, omicron exhibits an inefficient use of the cellular protease TMPRSS2, which is required for proteolytic cleavage of the spike protein at the S2' site to liberate the fusion peptide, and relies more strongly on the endosomal uptake route (56), suggesting that ACE2/ TMPRSS2-expressing cells would no longer be as strongly preferred target cells.…”
Section: Discussionmentioning
confidence: 99%
“…Protein-focused DCC calculations suggested that the flexible RBM was the cause of the observed anti-correlated motions in the Omicron sub-lineage RBD, especially in BA.1, BA.2 and BA.3_12, and which was also reflected in the hACE2 protein. Previous studies have highlighted the increased binding affinity of the Omicron sub-lineage RBD to the receptor hACE2 protein compared to the reference virus [124, 126, 136, 137]. Here we hypothesize that the observed RBM flexibility favors increased interactions between the S RBD and the receptor hACE2.…”
Section: Discussionmentioning
confidence: 72%
“…It is evident from the interaction analysis that, in addition to the changes in residue centrality especially in CC and complex interaction distance, dynamicity of the Omicron sub-lineages predict better binding to the hACE2 host receptor compared to the WT. Prior studies have also shown that Omicron mutations in the RBD facilitate improved binding to the hACE2 compared to the WT virus [135, 136].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the all-atom MD simulations were carried out for the Wuhan and Omicron RBD-ACE2 complexes. Due to the significant role of long glycans in virus-host interactions [ 51 , 52 ], unlike previous studies [ 50 , 53 ] we performed a comparative study between glycosylated and non-glycosylated RBD-ACE2 complexes to evaluate the impact of the existence of glycans on the binding of RBD to ACE2. The RMSD, RMSF, radius of gyration and hydrogen bond analysis confirmed that the Omicron RBD-ACE2 complex is more stable than that of the Wuhan indicating the increased infectivity.…”
Section: Discussionmentioning
confidence: 99%